“Play to Lead” Board Game as A Potential Intervention to Promote Entrepreneurship Competences and Servant Leadership Skills in European Adolescents - Bonaiuto, Flavia; Perucchini, Paola; Placidi, Valerio; Faggioli, Silvia; Barroca, Ana; Ferot, Celine; Netz, Lea; Xie, Mei; Bonaiuto, Marino (Psychology Hub, 2023)
Gaming has been shown to encourage active learning settings that increase interest and motivation, and develop the awareness of engagement and improve various skills. However, there is a dearth of literature on how to nurture young entrepreneurs or leaders through a game. This study investigates the effects of “Play to Lead”, a self-designed board game, on entrepreneurship competences and servant leadership among compulsory schooling students in four European countries (Denmark, Estonia, Italy, and Portugal). A total of 222 adolescents completed a questionnaire measuring entrepreneurship competences (EntreComp) and servant leadership dimensions before and after playing the game. Paired-samples t-tests were used to compare the scores of the participants before and after the game. Pearson correlation tests were conducted to determine the relationship between participants’ game experience (i.e., “game satisfaction” and “game comprehension”) and their EntreComp and servant leadership scores. The results showed that the servant leadership skill scores of the students did not demonstrate significant improvement, and only three items from EntreComp’s “Ideas and Opportunities” and “Into Action” dimensions exhibited a significant enhancement. Besides, participants reported positive feedback in terms of “game satisfaction” and “game comprehension”, which were related to their EntreComp scores. However, these improvements were also contingent on country and age, highlighting the need for replication in diverse samples of adolescents. Nonetheless, this study is the first to demonstrate the potential of a board game in promoting entrepreneurship competences and servant leadership skills among mandatory schooling adolescents, with important implications for education policymakers and curriculum designers seeking to foster these skills in students.